Rare earth tantalate ceramic based on hydrothermal method and preparation method thereof

Rare earth tantalate ceramics were prepared by hydrothermal method, and the doping and proportion optimization of Ti, Hf, Zr were used to solve the problem of unsatisfactory fracture toughness of rare earth tantalate ceramic materials, and achieved high fracture toughness and low thermal conductivity ceramics Material, suitable for high temperature environments.

CN119263830AActive Publication Date: 2025-01-07KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411183898.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-07
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The fracture toughness of rare earth tantalate ceramic materials is not ideal, and they cannot maintain structural stability and thermal insulation under extreme high temperature conditions.

Method used

Rare earth tantalate ceramics are prepared by hydrothermal method. Through the co-doping of three metal cations, Ti, Hf, and Zr, and the proportion optimization of metal ions, it forms a ceramic material of (MO2)x-(Y3TaO7)1-x, and controls the Die size to improve fracture toughness.

Benefits of technology

It significantly improves the fracture toughness and low thermal conductivity of ceramic materials, and enhances its thermal insulation and thermal shock resistance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263830A_ABST
    Figure CN119263830A_ABST
Patent Text Reader

Abstract

The invention relates to the field of rare earth materials, and discloses a rare earth tantalate ceramic based on a hydrothermal method and a preparation method thereof, the chemical formula of the tantalate material is (MO2) x-(Y3TaO7) 1-x, wherein X is more than 0 and less than 0.2, and M is formed by mixing three metal cations of Ti, Hf and Zr according to equal molar content; the ceramic material is prepared by sintering TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder through a hydrothermal method. The composition and the preparation process of the rare earth tantalate ceramic are comprehensively optimized, so that the rare earth tantalate ceramic has high fracture toughness while having low thermal conductivity, and has important significance in the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rare earth materials, and in particular to a rare earth tantalate ceramic based on a hydrothermal method and a preparation method thereof. Background Art

[0002] Thermal barrier coatings (TBCs) are advanced materials used to protect high-temperature alloy substrates and are widely used in high-temperature equipment such as aerospace engines and gas turbines. The main function of TBCs is to insulate, extend the service life of the substrate, and improve its working efficiency. As a new type of thermal barrier coating material, rare earth tantalates (Y3TaO7, YTaO4, YTa3O9) show broad application prospects due to their excellent high-temperature stability, low thermal conductivity and good thermal shock resistance. In the Y2O3-Ta2O5 binary phase diagram: at high temperatures, as the ratio of Y2O3 and Ta2O5 continues to change, different types of rare earth tantalates can be formed at high temperatures. As the Y2O3 content decreases, the generated rare earth tantalates are as follows: Y3TaO7-YTaO4-YTa3O9.

[0003] The melting point of Y3TaO7 is higher than 2000℃. It has good phase stability in high temperature environment, is not prone to phase change, and can maintain structural stability under extreme high temperature conditions. At the same time, Y3TaO7 has low thermal conductivity, which makes it have excellent thermal insulation performance in high temperature environment. The high thermal expansion coefficient can reduce thermal stress and enhance the material's thermal shock resistance. However, Y3TaO7 does not have the ferroelastic domain toughening mechanism like YSZ and YTaO4, resulting in low fracture toughness of Y3TaO7. Summary of the invention

[0004] The present invention aims to provide a rare earth tantalate ceramic based on a hydrothermal method and a preparation method thereof, so as to solve the problem of unsatisfactory fracture toughness of rare earth tantalate ceramic materials in the prior art.

[0005] To achieve the above object, the present invention adopts the following technical solution: a rare earth tantalate ceramic based on a hydrothermal method, the chemical formula of the tantalate material is (MO2) x -(Y3TaO7) 1-x ; Wherein 0<X<0.2, M is a mixture of three metal cations of Ti, Hf and Zr in equimolar content; the ceramic material is sintered by a hydrothermal method through TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder.

[0006] Preferably, as an improvement, the purity of TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder are all ≥99.9%.

[0007] Preferably, as an improvement, a method for preparing rare earth tantalate ceramics based on a hydrothermal method comprises the following steps:

[0008] Step (1): weigh TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder according to proportion, add solvents respectively and stir for the first time to obtain a uniform solution A;

[0009] Step (2): mixing the solution A obtained in step (1) and stirring for a second time, while adding ammonia water (NH3·H2O) to adjust the pH value, to obtain solution B;

[0010] Step (3): placing the solution B obtained in step (2) in a reaction vessel for hydrothermal reaction to obtain solution C;

[0011] Step (4): washing and drying the solution C in step (3) to obtain powder D;

[0012] Step (5): molding the powder D in step (4) to form a block E;

[0013] Step (6): Sintering the block E in step (5) to obtain rare earth tantalate ceramics.

[0014] Preferably, as an improvement, in step (1), the solvent is ethanol or deionized water, and the mass ratio of the powder to the solvent is (1:10) to (1:20).

[0015] Preferably, as an improvement, in step (1), the rotation speed of the first stirring is 300-600 r / min, and the stirring time is 1-2 h.

[0016] Preferably, as an improvement, in step (2), the pH value is adjusted to 8-10.

[0017] Preferably, as an improvement, in step (2), the rotation speed of the second stirring is 600 to 1000 r / min, and the stirring time is 1 to 2 h.

[0018] Preferably, as an improvement, in step (3), the temperature of the hydrothermal reaction is 150 to 250° C., and the reaction time is 24 to 60 hours.

[0019] Preferably, as an improvement, in step (4), the washing liquid is ethanol or deionized water; the drying temperature is 80 to 100° C., and the drying time is 10 to 24 hours.

[0020] Preferably, as an improvement, in step (5), the holding pressure is 200-300 MPa, and the holding time is 2-4 min; in step (6), the sintering temperature is 1500-1700° C., and the sintering time is 3-5 h.

[0021] The principle and advantages of this solution are: in practical application, in this technical solution, the composition and preparation process of rare earth tantalate ceramics are comprehensively upgraded to address the problem of unsatisfactory fracture toughness of rare earth tantalate ceramic materials in the prior art. In the composition of rare earth tantalate ceramic materials, the thermodynamic properties of Y3TaO7 are optimized by co-doping three metal cations of Ti, Hf and Zr and optimizing the ratio of metal ions. In the technical research and development stage, the confirmation of the value range of X is one of the difficulties of this technical solution, which has a great correlation with the mechanical properties of the material. Studies have shown that when X is not within the restricted range, a large amount of second phase appears in the grains, which will lead to reduced material performance. In addition, in the preparation process, rare earth tantalate ceramics are sintered by hydrothermal method from TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder, and the hydrothermal method is used to control the size of the grains, so that the fracture toughness is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagrams of the rare earth tantalate materials prepared in Examples 1 to 4 of the present invention;

[0023] Figure 2 This is a SEM image of the rare earth tantalate material prepared in Example 4 of the present invention;

[0024] Figure 3 This is a thermal conductivity diagram of the rare earth tantalate materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0025] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0026] Program Overview:

[0027] A rare earth tantalate ceramic based on a hydrothermal method, the chemical formula of the tantalate material is (MO2) x -(Y3TaO7) 1-x ; Wherein 0<X<0.2, M is a mixture of three metal cations of Ti, Hf and Zr in equal molar content; the ceramic material is formed by sintering TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder through a hydrothermal method. The purity of TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder is ≥99.9%.

[0028] A method for preparing rare earth tantalate ceramics based on a hydrothermal method comprises the following steps:

[0029] Step (1): TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder are weighed in proportion, and ethanol or deionized water are added respectively at a mass ratio of powder to solvent of (1:10) to (1:20) for the first stirring to obtain a uniform solution A.

[0030] The rotation speed of the first stirring is 300-600 r / min, the stirring time is 1-2 h, and the purity of TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder is not less than 99.9%.

[0031] Step (2): Solution A obtained in step (1) is mixed and stirred for a second time, and aqueous ammonia (NH3·H2O) is added to adjust the pH value to 8-10 to obtain solution B.

[0032] The second stirring speed is 600-1000 r / min, and the stirring time is 1-2 h.

[0033] Step (3): placing the solution B obtained in step (2) in a reaction kettle, and performing a hydrothermal reaction in an electric heated blast drying oven to obtain a solution C, wherein the temperature of the hydrothermal reaction is 150 to 250° C., and the reaction time is 24 to 60 hours.

[0034] Step (4): Wash the solution C in step (3) with ethanol or deionized water, and dry at 80-100° C. for 10-24 h to obtain powder D.

[0035] Step (5): placing the powder D in step (4) in a mold and compacting it to form a block E, wherein the holding pressure is 200 to 300 MPa and the holding time is 2 to 4 minutes.

[0036] Step (6): Sintering the block E in step (5) to obtain rare earth tantalate ceramics, wherein the sintering temperature is 1500-1700° C. and the sintering time is 3-5 hours.

[0037] The method of this technical solution can be used to prepare (MO2) with low thermal conductivity and high fracture toughness x -(Y3TaO7) 1-x Rare earth tantalate ceramics.

[0038] In order to fully illustrate the low thermal conductivity and high fracture toughness of (MO2) prepared by the above method x -(Y3TaO7) 1-xRare earth tantalate ceramics are described in the following 6 groups of examples. The difference between each example lies in the value of x and the specific parameter settings of the preparation process, as shown in Table 1:

[0039] Table 1 List of specific parameters of embodiments 1 to 6 of the present invention

[0040]

[0041]

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that in this comparative example, only YCl3 powder and TaCl5 powder are added to the raw material powder, that is, the content of TiCl4 powder, ZrCl4 powder and HfCl4 powder is 0% mol.

[0044] Comparative Example 2

[0045] The difference between this comparative example and Example 1 is that in this comparative example, only YCl3 powder, TaCl5 powder and TiCl4 powder are added to the raw material powder, that is, the content of ZrCl4 powder and HfCl4 powder is 0% mol.

[0046] Comparative Example 3

[0047] The difference between this comparative example and Example 1 is that in this comparative example, only YCl3 powder, TaCl5 powder and ZrCl4 powder are added to the raw material powder, that is, the content of TiCl4 powder and HfCl4 powder is 0% mol.

[0048] Comparative Example 4

[0049] The difference between this comparative example and Example 1 is that in this comparative example, only YCl3 powder, TaCl5 powder and HfCl4 powder are added to the raw material powder, that is, the content of TiCl4 powder and ZrCl4 powder is 0% mol.

[0050] Comparative Example 5

[0051] The difference between this comparative example and Example 1 is that in this comparative example, X=0.2.

[0052] Comparative Example 6

[0053] The difference between this comparative example and Example 1 is that in this comparative example, 0.005 mol HfCl4 powder, 0.01 mol TiCl4 powder and 0.015 mol ZrCl4 powder were added.

[0054] Comparative Example 7

[0055] The difference between this comparative example and Example 1 is that in this comparative example, 0.01 mol HfCl4 powder, 0.01 mol AlCl3 powder and 0.01 mol ZrCl4 powder are added.

[0056] Experimental Example 1 XRD Characterization

[0057] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 7 were tested using an X-ray diffractometer. Taking the rare earth tantalate material obtained in Examples 1 to 4 as an example, its XRD spectrum is as follows: Figure 1 As shown, the diffraction peaks of the XRD test results of Examples 1 to 4 correspond to the standard peaks of their standard PDF card #38-1413, and there is no second phase diffraction peak, indicating that the prepared sample is a single-phase rare earth tantalate material. At the same time, it can be seen that the main peak of 2θ≈30° shifts to the right with the increase of the doping amount, because the lattice expansion caused by the doping of Ti, Zr, and Hf ions into the Y3TaO7 lattice causes the XRD main peak to shift to the right.

[0058] Experimental Example 2 SEM Characterization

[0059] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 7 were tested using a scanning electron microscope. Taking the rare earth tantalate material obtained in Example 1 as an example, its SEM spectrum is as follows: Figure 2 As shown, according to Figure 2 It is observed that there are no pores in the crystal structure of rare earth tantalate materials, the grains are evenly distributed and the grain boundaries are clear, the grains are well bonded, and the grain size is 1 to 3 microns, which is smaller than the grain size obtained by the solid phase method. The rare earth tantalate materials prepared by the hydrothermal method can reduce the grain size, thereby improving the fracture toughness.

[0060] Experimental Example 3 Thermal Conductivity Detection

[0061] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 7 are ground into The thermal conductivity of the circular thin film is measured by a laser thermal conductivity meter. Taking the ceramic blocks prepared in Examples 1 to 3 and Comparative Example 1 as an example, the curve of the thermal conductivity changing with temperature is shown as follows: Figure 3 As shown in the figure, it can be seen that as the temperature continues to rise, the thermal conductivity of the ceramic blocks prepared in Examples 1 to 3 and Comparative Example 1 all decreases sharply, indicating that the thermal conductivity is excellent at high temperatures. However, the thermal conductivity of Examples 1 to 3 at high temperatures is lower than that of Comparative Example 1, reaching a minimum of 1.1 W·m -1 ·K -1 ,900℃. It shows that due to the incorporation of Ti, Zr, and Hf ions, lattice distortion occurs, resulting in strong phonon scattering, which reduces the mean free path of phonons and greatly reduces thermal conductivity.

[0062] Experimental Example 4 Fracture toughness test

[0063] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 7 were polished, and the fracture toughness of the tantalate ceramics was calculated using the indentation method. The specific method is: the polished ceramic block is indented with a Vickers hardness tester at a certain load (F) to obtain the hardness (H), and each sample is performed 10 times; then the indentation diagonal length (a) and the crack length (c) along the diagonal extension of the crack are obtained from the scanning electron microscope image; using the formula E is Young's modulus, used to calculate the fracture toughness (the average value of 10 times is taken for each sample). The calculation results are shown in Table 2. It can be seen that the average fracture toughness of Examples 1 to 6 is at least 56% higher than that of Comparative Examples 1 to 4. This is due to the small grains. At the same time, the three metal cations of Ti, Hf and Zr have a solid solution strengthening effect, which improves the fracture toughness. Comparative Example 5 exceeds the range of X, resulting in the production of a second phase at the grain boundary, which reduces the fracture toughness. The results of Comparative Examples 6-7 show that the ratio and type of metal cations have a great influence on the fracture toughness, especially when the type of metal cations is replaced, the fracture toughness of Comparative Example 7 is significantly reduced to only 2.13.

[0064] Table 2 Fracture toughness (n=3)

[0065] <![CDATA[Average fracture toughness (MPam 0.5 )]]> Example 1 3.95 Example 2 4.02 Example 3 4.14 Example 4 4.21 Example 5 4.19 Example 6 4.17 Comparative Example 1 2.47 Comparative Example 2 2.52 Comparative Example 3 2.23 Comparative Example 4 2.41 Comparative Example 5 3.12 Comparative Example 6 2.76 Comparative Example 7 2.13

[0066] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A rare earth tantalate ceramic based on a hydrothermal method, characterized in that: The chemical formula of tantalate material is (MO2) x -(Y3TaO7) 1-x ; Wherein 0<X<0.2, M is a mixture of three metal cations of Ti, Hf and Zr in equimolar content; the ceramic material is sintered by a hydrothermal method through TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder.

2. The rare earth tantalate ceramic based on the hydrothermal method according to claim 1, characterized in that: The purity of the TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder is ≥99.9%.

3. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 1 or 2, characterized in that: The steps include: Step (1): weigh TaCl5 powder, YCl3 powder, TiCl4 powder, ZrCl4 powder and HfCl4 powder according to proportion, add solvents respectively and stir for the first time to obtain a uniform solution A; Step (2): mixing the solution A obtained in step (1) and stirring for a second time, while adding ammonia water (NH3·H2O) to adjust the pH value, to obtain solution B; Step (3): placing the solution B obtained in step (2) in a reaction vessel for hydrothermal reaction to obtain solution C; Step (4): washing and drying the solution C in step (3) to obtain powder D; Step (5): molding the powder D in step (4) to form a block E; Step (6): Sintering the block E in step (5) to obtain rare earth tantalate ceramics.

4. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 3, characterized in that: In step (1), the solvent is ethanol or deionized water, and the mass ratio of the powder to the solvent is (1:10) to (1:20).

5. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 4, characterized in that: In step (1), the rotation speed of the first stirring is 300-600 r / min, and the stirring time is 1-2 h.

6. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 5, characterized in that: In step (2), the pH value is adjusted to 8-10.

7. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 6, characterized in that: In step (2), the second stirring speed is 600-1000 r / min, and the stirring time is 1-2 h.

8. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 7, characterized in that: In step (3), the temperature of the hydrothermal reaction is 150 to 250° C., and the reaction time is 24 to 60 hours.

9. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 8, characterized in that: In step (4), the washing liquid is ethanol or deionized water; the drying temperature is 80 to 100° C., and the drying time is 10 to 24 hours.

10. The method for preparing rare earth tantalate ceramics based on a hydrothermal method according to claim 9, characterized in that: In step (5), the holding pressure is 200-300 MPa, and the holding time is 2-4 min; in step (6), the sintering temperature is 1500-1700° C., and the sintering time is 3-5 h.

Citation Information

Patent Citations

  • Rare earth tantalate (RE3TaO7) thermal barrier coating and preparation method thereof

    CN111908921A

  • High-entropy carbide ceramic precursor, high-entropy carbide ceramic and preparation method

    CN115772034A

  • Tantalate crystal particle, method of manufacturing tantalate crystal particle, and dye-sensitized solar cell

    JP2009252658A

  • Maintaining coercive field after high temperature anneal for magnetic device applications with perpendicular magnetic anisotropy

    US10014465B1

Cited By

  • Preparation method of Y3TaO7 transparent ceramic with high refractive index and high optical quality

    CN122403984A